System prawno-administracyjny, modele i sposoby prowadzenia gospodarki odpadami w gminach (ogólne wiadomości) - Antoni Skowroński (Studia Ecologiae et Bioethicae)
The article touches actual principles and ways of waste economy leading in community. Community (Gmina) is a basic territorial unit of a local government which is obliged for environmental protection including assurance of cleanliness at its territory. The task can be fulfilled in different ways allowing actual rules of community, national and local rights. Pertaining to the rights, the article shows the analysis of legal and administrative aspects and in a synthetic way gathers and displays stages and methods of waste economy leading in community.